Life's essential 8, genetic susceptibility, and risk of inflammatory bowel diseases: a population-based cohort study - Honghao Yang; Qing Chang; Chao Ji; Gang Zheng; Zheng Ma; Liangkai Chen; Yang Xia; Yuhong Zhao (BMC, 2024)
Abstract Background Evidence has shown that the individual metrics in Life's Essential 8 (LE8), an updated cardiovascular health (CVH) concept proposed by the American Heart Association, play a role in the development of inflammatory bowel disease (IBD). However, epidemiological evidence on the overall LE8 on IBD risk remains limited. We aimed to assess the longitudinal associations of LE8-defined CVH and the risks of IBD and its subtypes, ulcerative colitis (UC) and Crohn's disease (CD). We also tested whether genetic susceptibility could modify these associations. Methods A total of 260,836 participants from the UK Biobank were included. LE8 scores were determined by 8 metrics (physical activity, diet, nicotine exposure, sleep, body mass index, blood pressure, blood glucose, and blood lipids), and were divided into three levels: low CVH (0-49), moderate CVH (50-79), and high CVH (80-100). Cox proportional hazards models were used to calculate the hazard ratios (HRs) and confidence intervals (CIs) of the risk of IBD in relation to CVH status. Results Over a median follow-up 12.3 years, we documented 1,500 IBD cases (including 1,070 UC and 502 CD). Compared to participants with low CVH, the HRs (95% CIs) of those with high CVH for IBD, UC, and CD were 0.67 (0.52, 0.83), 0.70 (0.52, 0.93), and 0.55 (0.38, 0.80), respectively. These associations were not modified by genetic susceptibility (all P for interactions > 0.05). The lowest HR (UC: 0.30, 95% CI: 0.20-0.45; CD: 0.33, 95% CI: 0.20-0.57) was observed in participants with both high CVH and low genetic risk. Conclusions Better CVH, defined by LE8, was associated with significantly lower risks of IBD, UC, and CD, irrespective of genetic predisposition. Our results underscore the importance of adherence to LE8 guidelines for maintaining CVH as a potential strategy in the prevention of IBD.